Fee Surcharge - McIntyre, Chuck; California Community Colleges, Sacramento. Office of the Chancellor ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1983)
In March 1983, the California Postsecondary Education Commission recommended that the Board of Governors of the California Community Colleges authorize community college districts to levy at their discretion a fee surcharge of not more than 10% of a mandatory general student charge. The objectives of levying the surcharge would be to increase district discretion in raising revenue, to improve district equity and resource allocation, and to support high priority educational needs in the district. An analysis of the proposed fee surcharge by the Chancellor's Office suggests that: (1) the impact of the surcharge on enrollment is likely to be negligible; (2) the surcharge is not a significant revenue-raising alternative; (3) the impact on district resource allocation is uncertain; (4) the impact on district funding equity would be insignificant; (5) the surcharge could have a regressive impact, burdening low-income students; and (6) financial flexibility can be better achieved through alternatives such as increased private financial support and expanded ways of raising local tax revenues. Therefore, the Chancellor's Office concluded that the objective of improved community college resource allocation would be better met through revenue-use flexibility rather than revenue-raising flexibility, and that the surcharge should not be adopted. District enrollment and financial data are appended. (LL)
ERIC Note: Discussed as Agenda Item 7 at the Meeting of the Board of Governors of the California Community Colleges (Sacramento, CA, June 2-3, 1983).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Community Colleges; Educational Equity (Finance); Educational Finance; Fees; Financial Policy; Financial Support; Private Financial Support; Resource Allocation; School District Autonomy; Statewide Planning; Student Costs; Tax Effort; Two Year College Students; Two Year Colleges; California; Opinion Papers; Numerical/Quantitative Data